Severe fires alter the outcome of the mutualism between ants and a Neotropical savanna tree. (9th September 2020) - Vasconcelos, Heraldo L; Koch, Elmo B A; Camarota, Flávio; Tito, Richard; Zuanon, Lino A; Maravalhas, Jonas
Abstract: Physical disturbances, such as fire, may affect the relationship between ants and plants. We evaluated the extent to which severe fires alter the protective effect of ants against the herbivores of an extrafloral-nectary bearing tree. We performed an ant removal experiment and sampled the ant fauna from the same trees over 4 years: the pre-fire year, the fire-year, and again 1 and 2 years later. Ants reduced insect herbivory in the pre-fire year and in the fire-year but failed to provide any plant protection in the two years after fire. The magnitude of the ant effect on herbivory did not differ between the pre-fire year and the fire-year. Fire reduced the abundance of ants with strictly arboreal-nesting habits. However, in the fire year (but not in the subsequent ones), this decline was compensated by an increase in the abundance of arboreal generalists and ground-nesting ants foraging in trees. Our results indicate that severe fires can affect the strength and direction of the ant effects on herbivory by altering the structure of the arboreal ant community and the abundance of insect herbivores. Fire disturbance is thus an important factor of conditionality of ant-plant mutualisms in fire-prone habitats, like the Cerrado savannas.